Plan de marketing para la hostería La Cascada del Cantón Chinchipe, Provincia de Zamora Chichipe - Jaramillo Troya., Luisa Alexandra (2016)
This research was made in the inn "La Cascada" in Canton Chinchipe , Zamora Chinchipe, this is intended to contribute to organizational development since during this time has not been developed and implemented a marketing plan , which does not allow business development to increase sales and advertising , have a better position and market share, look for different strategies to provide alternative solutions to the problems that arise within the company and thereby strengthen its image and quality of service. The research methodology for the development of the marketing plan was formulated based on the information collection personnel, internal and external factors and variables. Applied techniques such as interview, survey and direct observation to the manager and key informants. The main findings of the study were: in the external analysis was obtained as a result of the evaluation matrix of external factors, it has 8 opportunities where higher value are government policies to promote tourism in Ecuador and the interest rate it is maintained, as has fixed clients; threats are also 8 higher value consumer purchasing power is high, economic slowdown in the country giving a 2.77 weighted result of higher than average. In the competitive analysis it was obtained as a result of the competitive profile matrix as it has advantages in service quality, quality policies, customer loyalty giving a weighted value of 2.69 was found above its competition. The internal analysis was obtained as a result of the evaluation matrix of internal factors with 8 strengths where higher value are competitive prices, own infrastructure, being the only one in town, and 8 weaknesses the higher value this lack of advertising, possible creations similar companies; with a weighting of 2.74 demonstrating the need to develop strategies to help mitigate threats and weaknesses detected. In the SWOT analysis matrix which is analyzed, observed and described as the strengths and weaknesses interact with the threats and opportunities to identify strategies. In the internal and externalmatrix it was made according to the results of the evaluation matrix of external factors and internal evaluation matrix factors where it is located in the quadrant V retain and maintain. Matrix Competitive Position which was made based on the attractive market and competitive position already identified in the external analysis and competitive analysis giving a result that the SBU 1 has a value of 65% and SBU 2 a value of 35% placing strategic business units 2 in a lower position. Based on all the analyzes, we proceed to the preparation of the proposed marketing plan in order to lead the company to improve, the same containing objectives, strategies, goals, actions, policy makers and budget the objectives. Upon completion of the research work is important to draw conclusions, same that are designed to meet the project objectives, one of which is that the preparation of this Plan Marketing is intended to lodge the Cascada has greater positioning and market share Local, increase their income and improve their image. It is for this reason that the budget for the implementation of this plan have a total cost of $ 4,435.00, recommendations for the lodge Waterfall, bibliography and annexes format and interview survey indicated applied are also presented during research.